A Rare Case of Congenital Bilateral Upper Eyelids Ectropion in Down’s Syndrome : Conservative or Operative? Poster Presentation - Case Report - General practitioner - Mischka Scalvinni Suvero Suyar; Nazhira Janani; Ferdian Ramadhan; Balgis Desy Sulistyowati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Congenital upper eyelids ectropion, is a very rare congenital condition characterized by everted upper eyelids associated with Ichthyosis, Blepharophymosis Syndrome, birth trauma and prominently appears in Down’s syndrome. This case aimed to report a rare case of congenital ectropion in an Down’s syndrome with further management considerations, conservative or operative. Case Illustration : A three-month-old baby with bilateral red upper eyelids swelling since birth with conjunctival swelling followed by yellowish discharge. Born through section caesarean from a mother with history of pre-eclampsia and being incubated for 24 days. Ophthalmic examination revealed bilateral upper eyelids eversion, minimal conjunctival chemosis, epicantal fold. The upper eyelids able to be repositioned in relaxed state and re-everted with forced lid closure. Treatment of the eyelids eversion was conservative, combining antibiotics, topical steroids and lubricants. We referred to the pediatrician for the management of Down’s Syndrome, the further management for the eyelids eversion still debatable. Discussion : Most infants with congenital ectropion showed excellent anatomic and functional results with conservative treatment if managed timely and promptly. However, infants with Down’s syndrome have a more complicated course due to complex periorbital anatomy and facial anomalies such as flattened face, almond shaped eyes and large nose’s bridge. If congenital ectropion accompanied by lagophthalmos and exposure keratopathy, surgical management should be considered. Conclusion : Congenital eyelids ectropion can be managed conservatively or surgically depend on the clinical courses. Mild case able to be managed conservatively with excellent results if managed timely but surgical management supposed to be considered in complicated case.